Social media e-cigarette exposure and e-cigarette expectancies and use among young adults. (March 2018) - Pokhrel, Pallav; Fagan, Pebbles; Herzog, Thaddeus A.; Laestadius, Linnea; Buente, Wayne; Kawamoto, Crissy T.; Lee, Hye-Ryeon; Unger, Jennifer B.
Abstract: A vast majority of U.S. young adults use social media such as Facebook and Instagram daily. Research suggests that young adults are commonly exposed to e-cigarette-related marketing or user-generated content on the social media they use. Currently, however, there is limited empirical evidence as to how social media e-cigarette exposure is associated with e-cigarette use beliefs and behavior. In particular, limited evidence exists to support the proposition that social media e-cigarette exposure is uniquely associated with e-cigarette use, even after adjusting for the effects of e-cigarette use in young adults' in-person or 'offline' social networks. This study was conducted to test the hypotheses that 1) social media e-cigarette exposure is associated with e-cigarette use outcome expectancies and current e-cigarette use; and 2) the association between social media and e-cigarette use is linked via outcome expectancies. We collected cross-sectional data from a sample of 470 young adult college students in Hawaii. Hypotheses were tested by fitting a structural equation model to the data. The model accounted for the associations of demographic variables, cigarette smoking history, as well as e-cigarette use in individuals' actual social networks with expectancies and behavior. Results indicated that social media e-cigarette exposure was associated with current e-cigarette use indirectly through two of the four positive outcome expectancies examined, namely, positive "smoking" experience and positive sensory experience. We discuss the implications of the findings in the context of tobacco control efforts. Highlights: Social media e-cigarette exposure is associated with e-cigarette use. The association is independent of the effects of e-cigarette use in in-person social networks. The association is mediated by beliefs that e-cigarettes offer a better 'smoking' alternative. Findings draw attention to e-cigarette marketing content on social media.